Microbial Fuel Cell an Alternative for Sustainable Energy Production: Substrate, Challenges and Application - Saraf, Renuka; Goyal, Ayushi; Jain, Divya; Dutt, Kakoli (Current Green Chemistry, 2025)
The concept of bioelectricity has been known for over half a century. Its modern application in the form of a battery or fuel cell utilizing microbes and degradable organic molecules opens up a new domain of energy production in the form of Microbial fuel cells (MFC). This technology not only supports the sustainable development goals by being green and but also facilitates the utilization of a wide range of biosubstrates, leading to coupled applications like wastewater treatment, desalination, etc. The development of viable models of MFC and their possible scale-up for use is a major focus of the researchers as the global energy crisis increases and the search for alternatives widens. The construction, configuration, electrodes, electrolytes, and microorganisms used play a very relevant role in determining the performance, longevity, and utility of MFC. Furthermore, exploration of the underlying biochemical mechanisms and influence of MFC components on it leading to variabilities in coulombic efficiencies and power output are key areas underlying its development. This review attempts to present a cohesive summary of important achievements in the development of MFC research attempted globally.
Keywords: Microbial fuel cell